Desigualdades sociespaciais de Goiânia- GO: análise com base nos setores censitários subnormais - Lídia Milhomem Pereira (2019)
Today, the national urbanization process is continuous and expansive. Goiania, the Goias´ capital, is seen as an attractive economy metropolis in constant growth. Distant 209 km from Brasilia, the nation’s capital, it was initially planned for 50 thousand people and it has exceeded the prediction in less than sixty years. Nowadays, its population has reached more than 1.400.000 inhabitants. Nevertheless, in the last few years, it is verified the presence of occupation in places, that were primarily devalued, with the advance and appreciation of the urban space. Part of this study is to understand Goiania´s social space inequality, under the process of urban appreciation, city discussion, planning, space analysis, contextualizing with the dialectical realities under the perspective of capitalism. The main goal is to intensify the urban space discussions since the social space segregation process analysis and inequality, in the formation of distinct space in the city of Goiania-GO, using geotechnology. Therefore, this thesis is concerned about verifying if there is, in fact, subnormal clusters in Goiania. The research is also supported by quantitative methods and software such as Arc Gis and Q Gis, considering it is a quantitative methodology, using exploratory descriptive analysis. Census data were used, according to the planned methodological procedure. Through mappable components, the results generated by standard and nonstandard irregular occupations, indicate information from variable assemblage and indicators about the social space exclusion/inclusion/inequality. The methodological procedures consist of the following stages: detailing, selection, screening, sampling, variables and indicators description, k-means method application, Two Step Clusters and discriminative analysis validation. As a result, it was possible to understand that, although the city does not have a bumpy geomorphology and in the state of Goias it has been identified unexpressive number of subnormal clusters, which does not mean poverty, spatially the characteristics are not perceived in a sheer way. This is consequence from a highlevel inequality and development, such as different ways of living and social relations. Also, in places where there are subnormal clusters, the conditions related to its infrastructure, indicators and variables are very similar to the outskirts of town. Concomitantly, there are several unique and plural elements in the city and also a majority concentration in certain urban spaces from people belonging to the same social class. These, in most cases, are concentrated in specific neighborhoods or private condominiums, where it is possible to verify the presence of other social class components nearby, some even opposites. This research aims to provide local and regional opportunities for organizing, directing, controlling 10 and structuring by the public authorities, research scopes and institutions, opening to dialogue and diagnoses in order to reduce socioeconomic differences and inequalities.